Development and evaluation of a psychological adjustment communication system for adolescents with polycystic ovary syndrome at a high risk of depression: A mixed-method study protocol - Tan, Huiwen; Gao, Li; Guo, Yunmei; Liu, Ying; Ding, Rui; Yan, Xin; Wang, Xueting; Wang, Yousha; Wang, Lianhong (Frontiers in Psychiatry, 2022)
Background Depression is a serious psychological disorder that causes substantial psychological and physical suffering in adolescents, contributes to over 50% of suicide attempts, and affects the health status and psychosocial functioning of 25% of the adult population. The prevalence of polycystic ovary syndrome (PCOS) in adolescents is 5.6∼11.04%, and the prevalence of depression in adolescents with PCOS is as high as 50–60%. Depression seriously affects the rehabilitation and quality of life of adolescents with PCOS. In this study, we present a protocol for a mixed-method study to develop and evaluate the effectiveness of a psychological adjustment communication system for reducing the prevalence of depression among adolescents with PCOS who are at a high risk of depression in China. This study utilizes social support theory to develop a mobile phone-based intervention for adolescents with PCOS at a high risk of depression. Methods This sequential exploratory mixed-method study consists of four consecutive phases. In the first phase, we will review the literature to understand the disease experience and needs of adolescents with PCOS to construct an initial psychological adjustment communication system. In the second phase, researchers will interview patients and their parents using purposeful sampling methods and semi-structured interviews to appropriately modify the psychological adjustment communication system. In the third phase, the Delphi method will be used to improve the psychological adjustment communication system. The fourth phase will employ a quantitative approach using a before-and-after design to measure the effectiveness of the system. Discussion The results of this study will indicate the effectiveness of the psychological adjustment communication system in adolescents with PCOS who are at a high risk of depression. Registration number ChiCTR2100050123.